Manajemen Media TV9: Telaah Perkembangan Bisnis Dakwah di Era Media Baru - Anggit Pamungkas; Umi Halwati (El Madani : Jurnal Dakwah dan Komunikasi Islam, 2023)
Da'wah of Islam using the media is a form of strategic application for Muslims regarding the need to spread Islamic teachings with a wider reach, so that it is hoped that it will be able to attract the interest of the general public to listen to the calls of Islamic teachings. Using media in da’wah is an innovative process in carrying out da'wah so that the "message of wisdom" conveyed can be conveyed well and optimally. Along with the development of information technology and globalization, the mass media industry is also experiencing significant changes. These changes are clearly visible in aspects of structure, work and operational mechanisms, and mass media content. This ultimately urges various media institutions to follow the business competition patterns of the media industry in order to survive. The tight competitive climate in the mass media industry ultimately has an effect on the increasingly strong values ??of economic interests (profit) over the idealistic values ??of the media. This research method is qualitative with a descriptive approach. The media management applied to TV9 is the same as other media companies, what makes TV9 different is that there is still an inherent Islamic boarding school culture, because it is a religious TV whose spirit was born from the Islamic boarding school students. Regarding media management activities related to market push issues and issues of public interest, among business interests and da'wah, it tends to be more towards a da'wah orientation because da'wah is the vision and mission of TV9 and most of its programs are da'wah programs